Pendidikan Bela Negara Mahasiswa Institut Transportasi dan Logistik Trisakti Sebagai Bentuk Pengabdian Masyarakat oleh Fakultas Kedokteran Militer Universitas Pertahanan RI Tahun 2025 - Yochanan, E.; W, F. Sukma; Wibowo, Markus (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The national defense education and training activities carried out for 4 days and 3 nights for students of the Trisakti Transportation and Logistics Institute (ITL) aim to shape character, physical and mental resilience, and instill national values ​​and national defense. This activity is held in two waves with an intensive theoretical and practical field provision approach. The materials provided include basic military regulations, national insight, leadership, basic knowledge of disaster management, basic life support (BHD), and night soldier simulations. This training is the result of collaboration between ITL Trisakti and the Faculty of Military Medicine, Indonesian Defense University and PMPP TNI. The results of the activities showed a significant increase in discipline, national awareness, disaster preparedness, and cooperation between students. This program is a model for fostering national defense based on university students that can be replicated to form a young generation that is tough and loves its homeland.